Acute Onset Asymmetric Sensorimotor Paraparesis: Not Always Spinal!. Issue 1 (June 2020) - Gupta, Dhananjay; R, Pradeep; Mehta, Anish; Javali, Mahendra; Acharya, Purshottam T.; Srinivasa, Rangasetty
Abstract: Objective: To report an atypical case of acute onset sensorimotor paraparesis secondary to bilateral cerebral stroke. Background: Acute onset paraparesis or paraplegia is usually secondary to a spinal cord disease. Central or cerebral causes of paraparesis are rare and include parasagittal and bilateral precentral lesions. Design/Methods: Case report and literature review. Results: A 65-year-old man presented with acute onset weakness of both lower limbs, associated with pins and needle sensation. On examination, he was found to have paraparesis (grade 2/5, both legs) and an asymmetric sensory loss in both legs and thighs. Spinal magnetic resonance imaging ruled out any compressive or noncompressive etiology. Magnetic resonance imaging of the brain showed an acute infarction in the bilateral cerebral hemisphere in both the pre- and postcentral gyrus. An angiogram of the brain revealed an aplastic right ACA-A1 with left ACA-A1 feeding bilateral A2. There was distal left ACA-A1 stenosis seen, the probable cause of bilateral stroke in this patient. The patient was treated conservatively and showed symptomatic improvement during the course of stay at the hospital. Conclusion: This case of acute paraparesis secondary to bilateral cerebral infarction demonstrates the need to always look for a cerebral cause. In patients with cerebral infarction, who present early to a hospital, it may provide a window for thrombolytic or endovascular therapy.